Budidaya Jamur Tiram Putih Menggunakan Limbah Pertanian dan Pengolahannya menjadi Produk Pangan untuk Meningkatkan Perekonomian UMKM Oemah Jamur Tangerang - Intan Cidarbulan Matita; Dipakalyano; Wahyu Irawati; Adolf Jan Nexson Parhusip (JURNAL ComunitÃ Servizio : Jurnal Terkait Kegiatan Pengabdian kepada Masyarakat, terkhusus bidang Teknologi, Kewirausahaan dan Sosial Kemasyarakatan, 2025)
One of the mushrooms commonly consumed by Indonesians is white oyster mushroom because it is affordable and can fulfil daily protein needs. However, the production of white oyster mushrooms in Tangerang has decreased due to the rising cost of raw materials, particularly sawdust, used in making mushroom growing media (baglog) This community service was carried out at UMKM Oemah Jamur Tangerang, located in Kemuning Village, Gang Mulya, Legok, Tangerang. The objective of this community service is to enhance the conomy of UMKM Oemah Jamur Tangerang by utilizing agricultural waste for white oyster mushroom cultivation and processing mushrooms into higher-value food products. The activities included socialization, technology implementation, mentoring and evaluation. The implementation of technology involved producing baglogs using agricultural waste such as corn cobs, coffee grounds, banana barrels, rice husks and rice grains, as well as processing mushroom into food products such as white oyster mushrooms crisps and mushroom meatballs. The results of this community service indicated that the use of corn cobs resulted din faster growth of mycelium with higher yields. Processing white oyster mushrooms into mushroom crisps and mushroom meatballs can also increased the mushroom’ market value, with distinctive texture and taste characteristics, while extending their shelf life.